O discurso CPERS/SINDICATO : um estudo da designação pelo "novo jeito de governar" de Yeda Crusius - Tombini, Sandra Roberta Catto (2010)
Our main purpose with the writing of this text is to analyze how the CPERS (a union) designates the government, the educational system and the teachers of the state of Rio Grande do Sul, as well as the effects of meaning produced by these designations. This union fights for the rights of teachers and for quality education, and its discourse shows an ideology which is contrary to the government, fact that can be realized because of the linguistic materiality that affects the views not only of the teachers who are members of the union, but of the whole society. This study is based on the Discourse Analysis (DA) theory, which has its basis in France and has been widely developed in Brazil. The DA theory is dedicated to the study of the discourse itself within a political perspective, incorporating elements of history, psychoanalysis and linguistics. We also analyze in this study whether the union subject position represents a group of people, as some sort of spokesperson, or whether it operates as an articulator between the CPERS and the government. The concepts of the DA theory are applied to a corpus extracted from the union newspaper Sineta. As a result, we have observed that the CPERS belongs to a union Discursive Formation (DF), being permeated by the voices of those who do not want to be oppresed. By designating the government, the teachers and the educational system, the newspaper brings other voices that carry meanings uttered in a union DF. Therefore, the newspaper has the role of link between the members of the union and the state, representing and defending the interests of the former